Selective transport of atomic excitations in a driven chiral-coupled atomic chain. (5th March 2019) - Jen, H H
Abstract: We theoretically investigate the flow of the atomic excitations in a driven chiral-coupled atomic chain with non-reciprocal decay channels. This one-dimensional system allows infinite-range dipole–dipole interaction, and enables directional guided modes of scattered light. Under a weakly driven condition, we are able to simulate the transport properties of atomic excitations between the left and right parts of the chain. In the steady states, the transport is highly dependent on the equidistant positions of the ordered array, the excitation field detunings, and the directionality of such chiral-coupled system. We discuss the parameter regimes which are resilient or sensitive to position fluctuations, and provide insights to precise and genuine state preparations. Furthermore, we study the effect of position fluctuations on the transport of excitations. Our results can shed light on deterministic state preparations and pave the way for many-body state manipulations in the driven and dissipative chiral-coupled systems.